Adsorption of a cationic water-soluble dye onto cationic Langmuir–Blodgett films via nano clay platelets: An efficient approach to control the H-dimer. (2nd January 2016) - Bhattacharjee, J.; Shil, A.; Hussain, S. A.; Bhattacharjee, D.
ABSTRACT: This communication reports the successful adsorption of a water-soluble cationic fluorescent dye Acridine Orange (AO) onto Langmuir–Blodgett (LB) films of a cationic amphiphile octadecylamine (ODA) in the presence of nano-clay platelets hectorite. Acridine orange (AO) has been widely used as a stainer for the characterization of biopolymers. But AO has a tendency to form non-florescent H-dimer even in the aqueous solution. Anionic nano-clay platelets hectorite played an important role in controlling the H-dimer formation of AO in the hybrid film. Effects of various parameters in the adsorption process were investigated in detail.